Ion Beams in Materials Processing and Analysis - Schmidt, Bernd; Wetzig, Klaus (Springer Vienna : Imprint: Springer, 2013)
A comprehensive review of ion beam application in modern materials research is provided, including the basics of ion beam physics and technology. The physics of ion-solid interactions for ion implantation, ion beam synthesis, sputtering and nano-patterning is treated in detail. Its applications in materials research, development and analysis, developments of special techniques and interaction mechanisms of ion beams with solid state matter result in the optimization of new material properties, which are discussed thoroughly. Solid-state properties optimization for functional materials such as doped semiconductors and metal layers for nano-electronics, metal alloys, and nano-patterned surfaces is demonstrated. The ion beam is an important tool for both materials processing and analysis. Researchers engaged in solid-state physics and materials research, engineers and technologists in the field of modern functional materials will welcome this text.